2021
DOI: 10.1016/j.psj.2020.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the housing environment and laying hen strain on tibia and femur bone properties of different laying phases of Hy-Line hens

Abstract: This study aimed to determine the effect of the housing environment and laying hen strain on tibia and femur properties. A 3 × 2 factorial arrangement of 3 housing environments (conventional cages [ CC ], enriched colony cages [ EC ], and free range [ FR ]) and 2 laying hen strains (Hy-Line W-36 [ W-36 ] and Hy-Line Brown [ HB ]) in a completely randomized design was conducted from 32 to 85 wk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Moreover, the content of dry matter and ash in tibia bone was studied by Yalcin et al (2001) , who analyzed the effect of strain in broiler chickens and concluded that this factor significantly influenced the content of dry matter and ash. Sharma et al (2021) found the same results in the effect of genotype on tibia ash content (nonsignificant effect of genotype). However, for femur bones, the ash content was calculated as significant among the genotypes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Moreover, the content of dry matter and ash in tibia bone was studied by Yalcin et al (2001) , who analyzed the effect of strain in broiler chickens and concluded that this factor significantly influenced the content of dry matter and ash. Sharma et al (2021) found the same results in the effect of genotype on tibia ash content (nonsignificant effect of genotype). However, for femur bones, the ash content was calculated as significant among the genotypes.…”
Section: Discussionsupporting
confidence: 67%
“…Considering the bone quality, scientific literature often focuses on the effect of nutrition ( Świątkiewicz et al, 2010 ) or housing system ( Tactacan et al, 2009 ). However, several studies, such as ( Riczu et al, 2004 ; Sharma et al, 2021 ), observed the effect of genotype. Sharma et al (2021) observed the genotype's effect on quality properties of the tibia bone, also confirmed that genotype significantly influenced bone length and fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hofmann et al (2020) stated that the housing environment potentially impacts the immune system of hens but recommended that the choice of an environmental enrichment in the production system should be determined according to the particular need of hens. Sharma et al (2021) suggested that housing environment has a profound influence on bone strength though it varies between strains. Li et al (2021) emphasized that environmental enrichments in laying hen housing system potentially decrease the damages associated with stress during their transportation (e.g., from growing to egg production pens, to slaughter plants).…”
Section: Hen Welfarementioning
confidence: 99%
“…In the Belgorod region, crosses of foreign selection are used at all industrial enterprises. These crosses differ in production, but the consumer's demand is also taken into account here [1,2].…”
Section: Introductionmentioning
confidence: 99%